IMPROVEMENT OF DIAGNOSTIC METHODS OF FEMALE OF CATS WITH PYOMETRA WITH THE HELP OF SONOGRAPHY - Вусик, Д. О. (Scientific Progress & Innovations, 2015)
During 2008–2014 years 221 cats were investigated with the help of sonographic method in Sumy veterinary center «Health». Primarily the ultrasound characteristic of morphological condition of the uterus of clinical healthy female of cats during anoestrus was determined by the sonographic method. Echogram of healthy uterus is characterized by equal and uniform walls, lack of visualization of cavities, medium or slightly reduced relative to the surrounding tissue echogenicity. The ovaries of healthy cats at sonographic research were not visualized. Sonogram of the uterus with pyometra is characterized by enlargement of uterine horns, thickening or enlargement of the uterus. The maximum diameter of the body and uterine horns made pursuant 2,4–5,8 cm. Expanding uterus was noted in all experimental animals with pyometra. This animal uterus width was 1,22±0,35 cm. Contents of uterus were hypoechoic or anechoic display, in some cases hypoechoic moderate graininess was marked.